The First Report of In Vitro Antifungal and Antibiofilm Photodynamic Activity of Tetra-Cationic Porphyrins Containing Pt(II) Complexes against Candida albicans for Onychomycosis Treatment - da Rosa Pinheiro, Ticiane; Dantas, Gabrielle Aguiar; da Silva, Jean Lucas Gutknecht; Leal, Daniela Bitencourt Rosa; da Silva, Ricardo Barreto; de Lima Burgo, Thiago Augusto; Santos, Roberto Christ Vianna; Iglesias, Bernardo Almeida [UNESP] (MDPI, 2023)
Onychomycosis is a prevalent nail fungal infection, and Candida albicans is one of the most common microorganisms associated with it. One alternative therapy to the conventional treatment of onychomycosis is antimicrobial photoinactivation. This study aimed to evaluate for the first time the in vitro activity of cationic porphyrins with platinum(II) complexes 4PtTPyP and 3PtTPyP against C. albicans. The minimum inhibitory concentration of porphyrins and reactive oxygen species was evaluated by broth microdilution. The yeast eradication time was evaluated using a time-kill assay, and a checkerboard assay assessed the synergism in combination with commercial treatments. In vitro biofilm formation and destruction were observed using the crystal violet technique. The morphology of the samples was evaluated by atomic force microscopy, and the MTT technique was used to evaluate the cytotoxicity of the studied porphyrins in keratinocyte and fibroblast cell lines. The porphyrin 3PtTPyP showed excellent in vitro antifungal activity against the tested C. albicans strains. After white-light irradiation, 3PtTPyP eradicated fungal growth in 30 and 60 min. The possible mechanism of action was mixed by ROS generation, and the combined treatment with commercial drugs was indifferent. The 3PtTPyP significantly reduced the preformed biofilm in vitro. Lastly, the atomic force microscopy showed cellular damage in the tested samples, and 3PtTPyP did not show cytotoxicity against the tested cell lines. We conclude that 3PtTPyP is an excellent photosensitizer with promising in vitro results against C. albicans strains.
Keywords: antibiofilm activity; Candida albicans; onychomycosis; photodynamic therapy; Pt(II) porphyrins